Internet-based vestibular rehabilitation versus written instructions after acute vertigo: A randomised controlled trial - Solmaz Surano; Ellen Lindell; Jan Mathé; Hugo Davidsson; Tatjana Tomanovic; Maria Bjurman; Erik Faergemann; Torbjörn Ledin; Anette Rostmark; Helena Grip; Fredrik Öhberg; Gabriel Granåsen; et al. (PLoS ONE, 2026)
Background Acute vestibular syndrome (AVS) causes sudden and continuous vertigo, dizziness, and postural instability and is a common reason for emergency department visits, most commonly due to vestibular neuritis and, in rare cases, stroke. Vestibular rehabilitation (VR) is an evidence-based exercise therapy that facilitates vestibular compensation and is effective in chronic vestibular disorders. However, evidence for VR in acute vertigo remains limited and, despite guideline support, it remains underused in practice. Internet-based VR has demonstrated benefit in chronic dizziness but has not been evaluated in acute vertigo. This study aimed to evaluate the efficacy of an internet-based VR tool compared with standard care (written instructions) in reducing vestibular symptoms after acute onset vertigo. Methods and Findings A multicentre, randomised, evaluator-blinded superiority trial was conducted across nine hospitals in Sweden. Adults with ongoing AVS were recruited within 1–7 days after symptom onset and randomised (1:1) to six weeks of internet-based VR with personalised, progressively adjusted home exercises or to written instructions for home-based VR exercises. The primary outcome was the between-group difference in vestibular symptoms at six weeks measured using the Vertigo Symptom Scale Short Form (VSS-SF; range 0–60), with a difference of ≥3 points prespecified as clinically significant. Secondary outcomes included dizziness-related disability, walking speed, and balance. Of 184 randomised participants, 183 were included in the analyses (94 online VR; 89 written instructions; median age 56 years). In the intention-to-treat analysis, both groups improved at six weeks, with no significant between-group difference (adjusted mean difference −2.0 points, 95% CI −4.9 to 0.9; p = 0.18). Per-protocol analyses were consistent (−1.7 points, 95% CI −4.7 to 1.3; p = 0.27). Over 12 weeks, both groups showed reduced vestibular symptoms and improved disability, balance, and walking speed, without significant between-group differences. No serious adverse events were attributed to the interventions, and compliance was high in both groups. Conclusions Internet-based VR was not superior to written instructions in reducing vestibular symptoms six weeks after acute onset vertigo. Both groups demonstrated improvement from baseline, with no statistically significant between-group differences. These findings suggest that ensuring access to vestibular rehabilitation exercises may be more important than the specific mode of delivery after acute onset vertigo, and internet-based tools represent viable alternatives for patients who prefer or may benefit from a digital format. Trial registration Clinicaltrials.gov NCT05056324. https://clinicaltrials.gov/study/NCT05056324 . Registered on September 24, 2021.